Topochemical fluorination of Sr3(M(0.5)Ru(0.5))2O7 (M = Ti, Mn, Fe), n = 2, Ruddlesden-Popper phases. - Romero, F; Bingham, P; Forder, S; Hayward, M (2013)
Reaction of the appropriate Sr3(M(0.5)Ru(0.5))2O7 (M = Ti, Mn, Fe), n = 2, Ruddlesden-Popper oxide with CuF2 under flowing oxygen results in formation of the oxide-fluoride phases Sr3(Ti(0.5)Ru(0.5))2O7F2, Sr3(Mn(0.5)Ru(0.5))2O7F2, and Sr3(Fe(0.5)Ru(0.5))2O(5.5)F(3.5) via a topochemical anion insertion/substitution process. Analysis indicates the titanium and manganese phases have Ti(4+), Ru(6+) and Mn(4+), Ru(6+) oxidation state combinations, respectively, while Mössbauer spectra indicate an Fe(3+), Ru(5.5+) combination for the iron phase. Thus, it can be seen that the soft fluorination conditions employed lead to formation of highly oxidized Ru(6+) centers in all three oxide-fluoride phases, while oxidation states of the other transition metal M cations remain unchanged. Fluorination of Sr3(Ti(0.5)Ru(0.5))2O7 to Sr3(Ti(0.5)Ru(0.5))2O7F2 leads to suppression of magnetic order as the fluorinated material approaches metallic behavior. In contrast, fluorination of Sr3(Mn(0.5)Ru(0.5))2O7 and Sr3(Fe(0.5)Ru(0.5))2O7 lifts the magnetic frustration present in the oxide phases, resulting in observation of long-range antiferromagnetic order at low temperature in Sr3(Mn(0.5)Ru(0.5))2O7F2 and Sr3(Fe(0.5)Ru(0.5))2O(5.5)F(3.5). The influence of the topochemical fluorination on the magnetic behavior of the Sr3(M(0.5)Ru(0.5))2O(x)F(y) phases is discussed on the basis of changes to the ruthenium oxidation state and structural distortions.